1982
DOI: 10.1152/jappl.1982.52.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Renin, aldosterone, and converting enzyme during exercise and acute hypoxia in humans

Abstract: The possibility that hypoxia might inhibit the secretion of angiotension-converting enzyme (ACE) would explain the low concentrations of aldosterone reported in humans at high altitude. To observe the effect of such a reduction in ACE concentration on the plasma aldosterone concentration (PAC) four subjects performed mild exercise throughout a 2-h study so as to elevate their plasma renin activity (PRA). After the first 60 min breathing air they were switched to breathing 12.8% O2 (4,000 an altitude equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 0 publications
1
34
1
Order By: Relevance
“…The role of hypoxia in activation of the renin-angiotensin system is controversial; whilst it potentiates exercise-induced activation of the system [31], it does not directly increase renin and angiotensin II at rest [32]. In the current study, no correlation has been identified between oxygen saturation and Pa,O 2 and renin or angiotensin II levels.…”
Section: Pathological Activation Of the Renin-angiotensin Systemcontrasting
confidence: 63%
“…The role of hypoxia in activation of the renin-angiotensin system is controversial; whilst it potentiates exercise-induced activation of the system [31], it does not directly increase renin and angiotensin II at rest [32]. In the current study, no correlation has been identified between oxygen saturation and Pa,O 2 and renin or angiotensin II levels.…”
Section: Pathological Activation Of the Renin-angiotensin Systemcontrasting
confidence: 63%
“…The statistical similarity of circulating ACE activity between the two groups may be further evidence of this difference when considering that ACE levels may be influenced by mountaineering and exposure to altitude. [24][25][26] We found that the I allelic frequency and I dominant genotypic distribution (II & ID) of ACE I/D polymorphism were significantly over-represented in the Sherpas compared to the non-Sherpas at low altitude, providing insight into the genetic background of these two groups. The prevalence of the I allele was commonly associated with low ACE activity in both groups irrespective of either ethnicity or altitude of residence.…”
Section: Genotypic Distributions and Allelic Frequencies Of The Ace Imentioning
confidence: 99%
“…28 On the other hand, ACE activity was within +/-10% of normal sea-level values in high-altitude adapted mountaineers after 2-4 weeks at 6,300 m. 35 All of this suggests that maintaining physiologic low-altitude ACE activity at high altitude, as found in our study, may contribute to adaptive physiology by contributing to an adaptive respiratory response to hypoxia, 8,36, maintaining normal pulmonary artery pressures, 34 and contributing to sodium and fluid balance. 28 The level of circulating ACE is, however, significantly influenced by environmental stimuli such as hypoxia, 24 mountaineering and altitude. [25][26][27] ACE activity in individuals may vary by more than 100% over 6 months, 37 suggesting that environmental factors indeed cause marked fluctuations.…”
Section: Genotypic Distributions and Allelic Frequencies Of The Ace Imentioning
confidence: 99%
“…However, it seems likely that, using only six subjects in total, the study was significantly underpowered. Small sample sizes (as low as four) (Milledge and Catley 1982), and differences in exercise protocols may similarly account for other (false) negative findings. Thus, Aldigier et al (1993) studied only eight subjects exercising at incremental workloads separated by equal rest periods , and Miura et al (1994) six males at Fig.…”
Section: Ace Activitymentioning
confidence: 99%
“…However, it has been proposed that ACE becomes rate limiting in situations when levels of substrate Ang I increase. Exercise is associated with a rise in levels of plasma renin substrate (Metsarinne 1988), which is thought to be consumed, on account of the associated rise in renin activity (Fyhrquist et al 1983;Kosunen and Pakarinen 1976;Milledge and Catley 1982), to yield a rise in Ang I levels (Arvay et al 1982). It is also known that when levels of Ang I are artificially elevated through infusion, Ang II levels may become ACE genotypedependent (Brown et al 1998;Ueda et al 1995).…”
Section: Ang II Responsementioning
confidence: 99%